The Role of the School Administrator in the Situation of Coronavirus 2019 Epidemic of Education Institutions under the Secondary Educational Service Area Office Nakhon Pathom - Chomsang, Manirat; Thongphubate, Thanong (Legal State Journal, 2023)
This research article aims to assess the role of school administrators in the situation of the COVID-2019 epidemic and to compare the role of school administrators in the situation of the COVID-2019 epidemic according to the highest educational level, work experience in current position and academic standing. This study employed a quantitativ research. The sample group consisted of 105 peoples, namely the director, the deputy director of the school, head of department/work group under The Secondary Educational Service Area Office Nakhon Pathom. Collect data using questionnaires. The statistics used in the data analysis were mean, percentage, standard deviation, one-way ANOVA and interpret the results of the data analysis. The results showed that (1) the role of educational institution administrators in the overall and individual roles in the situation of the COVID-2019 epidemic at the highest level and (2) the administrators of the educational institutions with the highest level of education, work experience in current position and different academic standings play a role in the overall and individual role in the situation of the COVID-2019 epidemic, there was a statistically significant difference at the .05 level.